Mentor-mentee relationships in academia: insights toward a fulfilling career - Tenorio-Lopes, Luana (Frontiers in Education, 2023)
Over my academic journey, I had the privilege of learning from insightful professionals in the field of Physiology and Neurosciences. During my graduate and postdoctoral training at seven universities in Brazil, the US, and Canada, my mentors were able to stimulate my curiosity and made me very enthusiastic about science, teaching, and mentoring. Despite the hurdles that researchers confront daily, having a supportive mentor in an inclusive workplace influenced my decision to pursue a career in academia. Unfortunately, for the vast majority of aspiring scientists, this is not the case. Engaging with colleagues from different fields and cultural backgrounds taught me how students always expected more from their mentors. Many studies have shown that high levels of attrition across STEM disciplines are indicative of this scenario. In this perspective article, I outline the findings of the ad hoc mentorship method, as well as my self-reflections on how we could conquer the major problems correlated with a research mentor-mentee relationship. I illustrate how communication, time, and environment constitute interrelated components that can be managed effectively to produce short and long-term results toward a fruitful partnership. Finally, I highlighted institutions' critical role in implementing effective mentorship practices, procedures, and policies that support mentors and students. These discussions on the importance of appropriate mentorship can assist all levels of mentors in creating a pleasurable pathway for knowledge transmission and contribute to ensuring that a more equal, diverse, and inclusive population of young scientists has the opportunity to excel in their professions.